Manual de procedimientos contables para pequeñas y medianas empresas (pymes) en el cantón La Maná provincia de Cotopaxi - Cunuhay Changoluiza, Silvia Verónica (2016)
The overall objective of this study was to develop a manual of accounting procedures so that most small and medium enterprises do not have a manual for this was applied a survery to 227 business owners prior to the results obtained in the research exist (3 Industrial companies, 125 commercial, 99 services), in which it focused on the Noble trading company for its extensive experience in the market, the owner of this company said it did not have adequate instructional manual procedures accounting, given the need was decided to develop this manual in the company with a structure of relevant processes through programs flow that meets all expectations and characteristics of a company that will support the accounting department as for people who work in it because with the design of this manual will enable progress, devélopment and organization´s development in order to carry out the financial information efficiently and effectively maximizing profits and thus help accelerate the development of the activities according the processes generated in each of the financial transactions....